Chemokines and chemokine receptors during COVID-19 infection - Khalil, Bariaa A.; Elemam, Noha Mousaad; Maghazachi, Azzam A. (Computational and structural biotechnology journal, 2021)
[Display omitted] Chemokines are crucial inflammatory mediators needed during an immune response to clear pathogens. However, their excessive release is the main cause of hyperinflammation. In the recent COVID-19 outbreak, chemokines may be the direct cause of acute respiratory disease syndrome, a major complication leading to death in about 40% of severe cases. Several clinical investigations revealed that chemokines are directly involved in the different stages of SARS-CoV-2 infection. Here, we review the role of chemokines and their receptors in COVID-19 pathogenesis to better understand the disease immunopathology which may aid in developing possible therapeutic targets for the infection.